# 演習問題

$\frac{dy}{dx}=2$

$\frac{dy}{dx}=x$

$\frac{dy}{dx}=3y$

$\frac{dy}{dx}=-2y$

$\frac{dy}{dx}=-\frac{2x}{y}$

$\frac{dy}{dx}=\frac{1+y}{1+x}$

$\frac{dy}{dx}=2y+3$

$\frac{dy}{dx}=3{x}^{2}y$

$\frac{dy}{dx}=4{x}^{2}$

$\frac{dy}{dx}=3x+1$

$\frac{dy}{dx}=5{x}^{3}-7{x}^{2}-x+5$

$\frac{dy}{dx}=xy$

$\frac{dy}{dx}=\frac{y}{x}$

$\frac{dy}{dx}=\mathrm{sin}x$

$\frac{dy}{dx}=\mathrm{cos}x$

$\frac{dy}{dx}=4\mathrm{sin}5x$

$\frac{dy}{dx}=6\mathrm{cos}2x$

$\frac{dy}{dx}=2{e}^{3x}$

$\frac{dy}{dx}=-\frac{\mathrm{cos}x}{\mathrm{sin}y}$

$\frac{dy}{dx}=\frac{1+{e}^{x}}{{e}^{x-y}}$

$\left({\mathrm{tan}}^{-1}y\right){y}^{\prime }=\frac{\sqrt{2-{x}^{2}}}{{x}^{2}-2}$

${y}^{2}dx-{x}^{3}dy=0$

$\sqrt{x-1}{y}^{\prime }=\frac{1}{\sqrt{y}}$

${y}^{\prime }=\frac{x{y}^{3}+x{y}^{2}}{{x}^{3}y-xy}$

${y}^{\prime }={sin}^{2}x\mathrm{sin}y\mathrm{cos}x$

$\frac{dy}{dx}=\frac{{e}^{y}}{{e}^{x}}$

$\left({y}^{2}+\mathrm{sin}y\right){y}^{\prime }+\mathrm{cos}x+{x}^{3}=0$

$\frac{dy}{dx}=\frac{1}{2xy}$

($x=1$,$y=1$ )

$\frac{dy}{dx}={e}^{2x}{e}^{3y}$      （$x=0$,$y=0$

$\frac{dy}{dx}=\mathrm{sin}x{cos}^{2}y$      ($x=\frac{\pi }{4}$,$y=0$)

$\frac{dy}{dx}=\frac{1+{y}^{2}}{\sqrt{1-{x}^{2}}}$      ($y=\sqrt{3}$,$x=\frac{1}{2}$)

$\frac{dy}{dx}=\frac{y}{x}$　　･･････(1)

$\frac{dy}{dx}=\frac{{y}^{2}}{{x}^{2}}$

$x\frac{dy}{dx}=x+y$

$xy\frac{dy}{dx}={x}^{2}+{y}^{2}$　･･････(1)

$x-2y+3x{y}^{\prime }=0$　･･････(1)

$x{y}^{\prime }=\frac{x}{y}\sqrt{{x}^{2}+{y}^{2}}+y$

$\left(xy+{x}^{2}\right){y}^{\prime }={y}^{2}$

$\left({x}^{2}+xy\right){y}^{\prime }={x}^{2}+4xy+3{y}^{2}$

${y}^{\prime }-y={e}^{x}$

${y}^{\prime }+\frac{y}{x}=x$

${y}^{\prime }+y=x$

$x{y}^{\prime }-y=3{x}^{4}+2{x}^{3}+{x}^{2}$

${y}^{\prime }=\mathrm{sin}x-y$

$\left(1-{x}^{2}\right){y}^{\prime }={x}^{2}-xy-1$

$x{y}^{\prime }+\frac{y}{\mathrm{log}x}=4{x}^{2}$

${y}^{\prime }-\left({e}^{{x}^{2}}+2xy+y\right)=0$

$\frac{dy}{dx}+y={y}^{2}$

$\frac{dy}{dx}+\frac{y}{x}={y}^{3}$

$\frac{dy}{dx}+xy=-x{y}^{3}$

$\frac{dy}{dx}-\frac{y}{2x}=\left(2{x}^{2}+1\right){y}^{3}$

$2ydx+\left(2x+1\right)dy=0$

$\left({y}^{2}+2xy+1\right)dx$$+\left({x}^{2}+2xy+y\right)dy$$=0$

$\left(y{e}^{x}-{y}^{2}\mathrm{sin}x\right)dx$$+\left({e}^{x}+2y\mathrm{cos}x\right)dy$$=0$

$\left(\frac{y}{x}+\mathrm{log}y\right)dx$$+\left(\frac{x}{y}+\mathrm{log}x\right)dy$$=0$

2階線形微分方程式に関する問題

${y}^{″}+2{y}^{\prime }+2y=0$

2階線形微分方程式に関する問題

${y}^{″}-5{y}^{\prime }+4y=0$

2階線形微分方程式に関する問題

${y}^{″}+2{y}^{\prime }+y=0$

2階線形微分方程式に関する問題

${y}^{″}+2{y}^{″}=0$

2階線形微分方程式に関する問題

${y}^{″}-5{y}^{\prime }+6y=0$

2階線形微分方程式に関する問題

${y}^{″}+{y}^{\prime }+y=0$

2階線形微分方程式に関する問題

${y}^{″}-2{y}^{\prime }+y=0$

2階線形微分方程式に関する問題

${y}^{″}+3y=0$

2階線形微分方程式に関する問題

${y}^{″}-10{y}^{\prime }+29y=0$

2階線形微分方程式に関する問題

${y}^{″}-10{y}^{\prime }+25y=0$

2階線形微分方程式に関する問題

${y}^{″}-{y}^{\prime }-2y=4{x}^{2}$

2階線形微分方程式に関する問題

${y}^{″}-{y}^{\prime }=-3{x}^{2}$

2階線形微分方程式に関する問題

${y}^{″}-{y}^{\prime }-2y=4{e}^{3x}$

2階線形微分方程式に関する問題

${y}^{″}+4y=4\mathrm{cos}2x$

2階線形微分方程式に関する問題

${y}^{″}-{y}^{\prime }-2y=18x{e}^{2x}$

2階線形微分方程式に関する問題

${y}^{″}-2{y}^{\prime }+2y=2{e}^{x}\mathrm{cos}2x$

2階線形微分方程式に関する問題

${y}^{″}-{y}^{\prime }-2y=9{e}^{2x}$

2階線形微分方程式に関する問題

${y}^{″}+{y}^{\prime }-2y={e}^{x}+2x$

${y}^{″}+2y=2{x}^{2}$

$\left({D}^{2}-5D+6\right)y=18x$